Pelatihan Penulisan Karya Ilmiah di SMAN 1 Narmada Tahun 2023 - Vici Handalusia Husni; Habiburrahman Habiburrahman; Ali Akbar Hidayat; Muhammad Dzul Fadlli; Muhamad Bai'ul Hak (Yayasan Literasi Sains Indonesia, 2023)
Teachers and students' interest in writing at SMAN 1 Narmada needs to be increased. This can be seen from the lack of scientific work produced by teachers and students from SMAN 1 Narmada. The holding of training on writing scientific papers at SMAN 1 Narmada aims to increase the interest and knowledge of teachers and students in writing scientific papers at the school and it is also hoped that it will not only have an impact on the school itself but also have an impact on impact schools, namely SMAN 2 Narmada and SMAN 1 Lingsar . The methods used in this training are lecture, question and answer and practice methods. The number of participants in this training was 50 people consisting of Mataram University students and teachers along with students from SMAN 1 Narmada, SMAN 2 Narmada and SMAN 1 Lingsar. This training was able to foster an interest in writing for teachers and students as evidenced by the creation of several works by the participants. Approximately 34% of participants consisting of teachers and students succeeded in drafting their scientific papers with very satisfactory review results.